Principles of heating, ventilation, and air conditioning in buildings - Mitchell, John W., 1935- 4 0 16; 1954- , Braun, James E.; 5 (Hoboken, N.J. : Wiley, 2013)
Heating Ventilation and Air Conditioning by J. W. Mitchell and J. E. Braun provides foundational knowledge for the behavior and analysis of HVAC systems and related devices. The emphasis of this text is on the application of engineering principles that features tight integration of physical descriptions with a software program that allows performance to be directly calculated, with results that provide insight into actual behavior. Furthermore, the text offers more examples, end-of-chapter problems, and design projects that represent situations an engineer might face in practice and are selected to illustrate the complex and integrated nature of an HVAC system or piece of equipment--Provided by publisher.
Machine generated contents note: 1. Introduction to Air-Conditioning Systems2. System Analysis Techniques and the Use of EES3. Thermodynamics and Fluid Flow in HVAC Applications4. Heat Transfer in HVAC Applications5. Psychrometrics for HVAC Applications6. Overview of HVAC Systems7. Thermal Comfort and Air Quality8. Weather Data, Statistics, and Processing9. Components of Building Heat Loss and Gain10. Heating and Cooling Loads11. Air Distribution Systems12. Liquid Distribution Systems13. Heat Exchangers for Heating and Cooling Applications14. Cooling Towers and Desiccant Systems15 Vapor-Compression Refrigeration and Air-Conditioning Systems16. Heat Pump Systems17. Thermal Storage18. Building and HVAC Energy Use19. HVAC Control Principles20. Supervisory Control21. Engineering Design Problems.
Includes bibliographical references and index.
Keywords: 2 -- 0; 6; Heating.;Ventilation.;Air conditioning. -- 20; 20; 2